1987
DOI: 10.1002/j.1460-2075.1987.tb02420.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure of an inverted duplication formed as a first step in a gene amplification event: implications for a model of gene amplification.

Abstract: Inverted duplications have been observed to be a common feature of gene amplification in mammalian cells and appear to be generated as a primary event in the amplification process (Ford etal., 1985; Ford and Fried, 1986). The structural features of the amplified inverted duplication, containing the polyoma virus oncogene middle T-antigen, were analysed in transformed 3B rat cells. No unusual sequences such as transposition elements were detected at the site of the inversion. The inversion was generated by a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
84
2
1

Year Published

1990
1990
2002
2002

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 29 publications
4
84
2
1
Order By: Relevance
“…Populations of SV40 defective genomes were shown to be supercoiled and relaxed circular DNAs of heterogenous sizes (9,28). In some cases the formation of extrachromosomal circles with inverted repeats was proposed to be one of the initial steps of gene amplification (45,51,66,67). Clearly, random overreplication of a portion of ori plasmid-the unstably amplified state-is not beneficial for the stability of the viral genome.…”
Section: Vol 76 2002 Notes 5839mentioning
confidence: 99%
“…Populations of SV40 defective genomes were shown to be supercoiled and relaxed circular DNAs of heterogenous sizes (9,28). In some cases the formation of extrachromosomal circles with inverted repeats was proposed to be one of the initial steps of gene amplification (45,51,66,67). Clearly, random overreplication of a portion of ori plasmid-the unstably amplified state-is not beneficial for the stability of the viral genome.…”
Section: Vol 76 2002 Notes 5839mentioning
confidence: 99%
“…6C), coupled with appropriate end ligation reactions, will produce circular amplicons and a broken chromosome terminated by sequences homologous to some of those in the amplicon. Circles produced by four breaks/ligations will contain imperfect inverted repeats of the type typically found in mammalian amplicons (Ford and Fried 1986;Saito and Stark 1986;Looney and Hamlin 1987;Passananti et al 1987;Hyrien et al 1988;Ruiz and Wahl 1988). The sizes of such extrachromosomal amplicons could easily conform to the majority of amplicon sizes detected at the CHO DHFR locus (Looney et al 1988).…”
Section: A Model For Gene Amplification Involving Chromosome Breakagementioning
confidence: 99%
“…In many cases characterized, these amplified regions contain large ''head-to-head'' duplications (palindromes) of sequences that can be tens to hundreds of kb in size (3)(4)(5)(6)(7)(8). Cytogenetic studies have further revealed that large inverted duplications of a chromosomal region are formed at early stages of gene amplification (9)(10)(11).…”
mentioning
confidence: 99%